Post office made House of Culture; adaptive reuse to strengthen world heritage - Delvéus, Erik (My University, 2024)
As In the pursuit of a more sustainable architectural practice, this thesis advocates for the adaptive reuse of existing structures and materials. Focusing on Karlskrona’s old post office, slated for demolition, the project proposes its transformation into a cultural center, preserving its historical significance while embracing the contemporary needs of the city. Through holistic design approaches, the project aimed to breathe new life into the building and site, celebrating its imperfections and challenges. The methodology integrates qualitative and quantitative approaches, including literature theory readings and extensive reviews of produced technical documents. It also involves an in-depth analysis of Karlskrona’s UNESCO world heritage classification and the development of architectural techniques specific to the project. By combining these methods, the thesis presents a transformation plan that showcases the potential of aesthetic integrity and contextual responsibility in architectural transformations. The project emphasizes the viability of transformation, demonstrating how it keeps and enhances the distinctive character and historical value of revitalized spaces. By embracing existing material beauty and imperfections, the design approach of approaching the project as a palimpsest seeks to create a contemporary cultural center while respecting the building’s own form and heritage. Ultimately, the proposal contributes to the broader discourse on architectural transformations in heritage city centers. It highlights the importance of intentional preservation and transformation in culturally significant areas of the built environment. By offering an alternative to the complete destruction of the original post office building, the project aims to strengthen Karlskrona’s UNESCO world heritage status while providing a space for the city’s inhabitants to gather, create, and celebrate culture.